Rod phosphodiesterase-6 PDE6A and PDE6B Subunits Are Enzymatically Equivalent - Muradov, Hakim (American Society for Biochemistry and Molecular Biology, 2010)
Phosphodiesterase-6 (PDE6) is the key effector enzyme of the phototransduction cascade in rods and cones. The catalytic core of rod PDE6 is a unique heterodimer of PDE6A and PDE6B catalytic subunits. The functional significance of rod PDE6 heterodimerization and conserved differences between PDE6AB and cone PDE6C and the individual properties of PDE6A and PDE6B are unknown. To address these outstanding questions, we expressed chimeric homodimeric enzymes, enhanced GFP (EGFP)-PDE6C-A and EGFP-PDE6C-B, containing the PDE6A and PDE6B catalytic domains, respectively, in transgenic Xenopus laevis. Similar to EGFP-PDE6C, EGFP-PDE6C-A and EGFP-PDE6C-B were targeted to the rod outer segments and concentrated at the disc rims. PDE6C, PDE6C-A, and PDE6C-B were isolated following selective immunoprecipitation of the EGFP fusion proteins. All three enzymes, PDE6C, PDE6C-A, and PDE6C-B, hydrolyzed cGMP with similar K(m) (20–23 μm) and k(cat) (4200–5100 s(−1)) values. Likewise, the K(i) values for PDE6C, PDE6C-A, and PDE6C-B inhibition by the cone- and rod-specific PDE6 γ-subunits (Pγ) were comparable. Recombinant cone transducin-α (Gα(t2)) and native rod Gα(t1) fully and potently activated PDE6C, PDE6C-A, and PDE6C-B. In contrast, the half-maximal activation of bovine rod PDE6 required markedly higher concentrations of Gα(t2) or Gα(t1). Our results suggest that PDE6A and PDE6B are enzymatically equivalent. Furthermore, PDE6A and PDE6B are similar to PDE6C with respect to catalytic properties and the interaction with Pγ but differ in the interaction with transducin. This study significantly limits the range of mechanisms by which conserved differences between PDE6A, PDE6B, and PDE6C may contribute to remarkable differences in rod and cone physiology.